Effect of simvastatin on MMPs and TIMPs in cigarette smoke-induced rat COPD model - Sun, Jiawei (Int J Chron Obstruct Pulmon Dis, 2017)
BACKGROUND: Proteases may play an important role in the development of chronic obstructive pulmonary disease and emphysema in response to cigarette smoke exposure (CSE). The current study was designed to investigate the expression of matrix metalloproteinase (MMP)-8, MMP-9, MMP-12, tissue inhibitor of MMP (TIMP)-1, and TIMP-4 in rat lung tissues in response to CSE, and assessed the effect of simvastatin in regulating expression of MMPs and TIMPs. METHODS: Thirty normal Sprague Dawley (SD) rats were divided into control (n=10), CSE (n=10), and CSE plus simvastatin (n=10) groups. Animals were whole-body exposed to the cigarette smoke in the box for 1 hour each time, twice a day, 5 days a week for 16 weeks. Animals of CSE + simvastatin group were intra-gastrically administered simvastatin at a dose of 5 mg/kg/day followed by CSE. Bronchoalveolar lavage fluid was harvested for inflammatory cell count and lung tissues were stained for morphologic examination. Expression of mRNA and protein level of MMP-8, MMP-9, MMP-12, TIMP-1, and TIMP-4 was assessed by real-time reverse transcription polymerase chain reaction and immunohistochemistry, respectively. RESULTS: CSE resulted in a significant increase of mean linear intercept (MLI: 34.6±2.0 μm) and bronchial wall thickness and diameter (BWT/D, 0.250±0.062) compared to control (MLI: 24.0±1.7 μm, BWT/D: 0.160±0.034, P<0.01). In contrast, mean alveolar number was significantly decreased in the CSE group than that in the control group (13.5±2.0 of CSE vs 21.5±2.0 N/μm(2) of control, P>0.01). Simvastatin slightly but not significantly prevented alteration of MLI, BWT/D, and mean alveolar number (MLI: 33.4±1.4 μm; BWT/D: 0.220±0.052; mean alveolar number: 15.5±2.5 N/μm(2), P>0.05). Total white blood cell was significantly increased in the bronchoalveolar lavage fluid of smoking group (3.3±2.5×10(9) cells/L vs 1.1±1.3×10(9) cells/L of control, P<0.01), and it was significantly reduced by simvastatin (2.3±2.1×10(9) cells/L, P<0.01). CSE resulted in significantly increased accumulation of neutrophils and macrophages (neutrophils: 14.5%±1.3% of CSE group vs 9.1%±1.5% of control; macrophage: 91%±3% of CSE group vs 87%±2% of control, P<0.05), and simvastatin significantly reduced neutrophils (12.9%±2.0%, P<0.05) in the bronchoalveolar lavage fluid, but had no effect on macrophage (89%±1.6%, P>0.05). In response to CSE, MMP-8, MMP-9, and MMP-12 mRNA were upregulated more than sevenfold, while TIMP-1 and TIMP-4 increased two- to fivefold. Simvastatin significantly blocked upregulation of MMP-8 and -9 (P<0.01), but had no effect on MMP-12, TIMP-1 and TIMP-4 mRNA (P>0.05). In addition, simvastatin significantly blocked cigarette smoke-induced MMP-8 and -9 protein synthesis, while it had no significant effect on TIMP-1 and -4 protein synthesis even in the presence of cigarette smoke. CONCLUSION: CSE resulted in imbalance of MMPs and TIMPs, and by which mechanism, cigarette smoke may lead to insufficient lung tissue repair. Simvastatin partially blocked airway inflammation and MMP production and, thus, statins may modulate composition of the lung extracellular matrix.